(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The fact that social norms are an integral part of the management of society, that social norms are a set of rules that harmonize the behavior of a person or social group with a certain social environment, the essence of serious changes and trends in the system of social norms in the period of the globe, the role of the principles of studying the – modern factors affecting the deviation of atvor – the internet, the virtual world, the analysis of the influx of information, the study of its sociological aspects and the study of the problems of young people indicate that in the process of globalization there are serious risks aimed at disrupting our spiritual life, and the development of measures to prevent them. Each of the social vices associated with drunkenness, drug addiction, self-killings, which are included in the Deviant types of behavior, have different aspects in essence according to the occurrence and social consequences. The first difference will be that long-lasting social harmful habits become an integral part of a deviant behavioral lifestyle. Constant family disagreement, dissatisfaction with the family and the environment, misunderstanding in the house, etc. – all this injures the psyche of the child and he tries to change the current situation. In this place, social control systems that prevent and combat the development of shortcomings, including conflicts, play a negative role in social institutions.